Convergence and a condition of humanities - Rutkiewicz, Paweł (Hybris, 2014)
I used the term “convergence” for describing a social condition of humanities in the face of hard science’s growing importance. I analyzed the term, derived from both sociology and media studies, in context of philosophical issues of globalization. Finally, I defined “convergence” as a matter of coexistence of the “old” and the “new” — where the latter determines the first’s way of development. On the basis of this statement I proposed a “convergent attitude” as a kind of solution for the weakening condition of humanities. The “convergent attitude” means the openness to technological and scientific modifications of everyday life as to the important interpretative context. The main frame of theoretical reference is Actor-Network Theory by Bruno Latour, which has been compared with Stanley Fish’s neopragmatism and with the theory of paradigms by Thomas Kuhn. I give some examples of “convergent attitude” from works by Stanisław Lem and Peter Sloterdijk.